Gone Home : Race and Roots through Appalachia - Brown, Karida, 1982- (Book collections on Project MUSE., 2018)
"Karida L. Brown's Gone Home offers a much-needed corrective to the current white-washing of Appalachia. In telling the stories of Appalachian African Americans living and working in steel and coal towns, Brown offers a deep and sweeping look at race, the formation of identity, changes in politics and policy, and black migration in the region and beyond"--